Cubic fluorite-based lanthanum cerium oxide thermal barrier top-coat fabrication, properties, and performance: Present status and prospects - Kandasamy, Praveen; Kim, Hee Jin; Sivakumar Govindarajan; Lee, Min Wook (Elsevier BV, 2024)
Lanthanum cerium oxide (La2Ce2O7, LC) is one of the emerging ceramic thermal barrier coatings (TBC) owing to its low thermal conductivity and a high coefficient of thermal expansion compared with conventional yttria-stabilized zirconia (YSZ). This review summarizes powder production, thermophysical properties, coating processes, thermal durability, mitigation against calcium magnesium alumino-silicate attack and volcanic ash, high-temperature corrosion, and doping of other rare-earth oxides to enhance their properties and performance. The advantages of developing hybrid, double-layered, and multi-layered coatings are discussed to improve the high-temperature corrosion resistance and lifetime of the coatings. The improved LC-TBCs for commercial usage and the prolonged life of components with improved properties are presented in detail.